EVALUATION OF THE PHYSICAL PROPERTIES OF GROUND AND BOUND IN O'ZAN WASH (Intent Research Scientific Journal, 2023)
On the basis of laboratory studies, the physical properties of the studied soils for erosion were established. The resistance of these soil properties is shown with the eroding ability of the water flow. A relationship has been established between the eroding flow rates and the intensity of erosion of cohesive soils.